Penerapan Model Pembelajaran Contextual Teaching and Learning (CTL) Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran PKn Kelas IV Sekolah Dasar - Risal M. Merentek; Dinny Poluan; Richard D. H. Pangkey; Mozes Y. Legi (Peneliti.net, 2023)
The purpose of this study was to improve student learning outcomes in the fourth grade civics education subject at GMIM Karowa Elementary School through the application of the Contextual Teaching and Learning learning model. The research method used in this research is classroom action research. The number of students who were the subject of the study was 16 students consisting of 9 male students and 7 female students. The research was conducted in II cycles and each cycle consisted of four stages, namely planning, implementing actions, observing, and reflecting. As for the first cycle, the percentage of achievement of learning outcomes was 67.18%. The results achieved in cycle I were still low, for this reason researchers made improvements in cycle II so that research results could increase. In cycle II, the percentage of achievement of learning outcomes increased to 86.25%. Based on the results obtained, it can be concluded that by using the Contextual Teaching And Learning (CTL) learning model it can improve student learning outcomes in the civics education subject for class IV SD GMIM Karowa